Assessment of Bioavailability Parameters of Mono- and Bistriazole Derivatives of Propynoylbetulin - Monika Kadela-Tomanek; Arkadiusz Sokal; Klaudia Stocerz; Ewa Bębenek; Elwira Chrobak; Paweł Olczyk (Applied Sciences, 2024)
Bioavailability describes the properties that determine the passage of a compound through biological barriers. In many cases, bioavailability depends on the lipophilicity of the compound. In this study, the lipophilicity as well as other bioavailability properties of the mono- and bistriazole derivatives of betulin are presented. The lipophilicity was determined using RP-TLC and theoretical methods. The experimental lipophilicity of mono- and bistriazole derivatives is in the range from 4.39 to 7.85 and from 3.75 to 8.83, respectively. The lipophilicity of mono- and bistriazoles is similar, and the logPTLC depends on the type of substituent at the triazole ring. The introduction of a substituent with oxygen and nitrogen atoms decreases lipophilicity. Comparing the experimental and theoretical lipophilicity shows that the milogP and XLOGP3 programs best reproduce the experimental values. The in silico-determined pharmacokinetic parameters show that monotriazole derivatives could be used as oral drugs while bistriazoles show low availability after oral administration. Triazoles could be used as transdermal drugs. The analysis of in silico bioavailability parameters shows that the type of substituent at the triazole ring influences the pharmacokinetic properties, while the number of triazole rings slightly affects the bioavailability properties of the compound.